Evolved Programmable Network - Greg Smith; Greg Nehib (Dianxin kexue)
The communications industry has undergone radical change over the past 30 years, moving from a business model that was largely built around offering bandwidth at fixed locations to one delivering seamless internet and application access anywhere. This success has been driven by continuous technical innovation in both computer （semiconductor）technologies along with improved optical and wireless transmission technology enabling faster and lower priced bandwidth. However, a new era in the industry is coming which is driven by cloud computing and trillions of newly connected devices, with the internet of everything. This will demand changes in the business models, network architectures, and technologies used by service providers if they are going to be successful in the future. These trends and how innovations meet these emerging requirements were analyzed and that can help network operators achieve their global business objectives.